A multistimulus-responsive self-healable supramolecular copper(ii)-metallogel derived from l-(+) tartaric acid: an efficient Schottky barrier diode. (25th August 2022) - Dhibar, Subhendu; Ojha, Saurav Kumar; Mohan, Aiswarya; Prabhakaran, Siva Prasad Chimminiankuttichi; Bhattacharjee, Subham; Karmakar, Kripasindhu; Karmakar, Priya; Predeep, Padmanabhan; Ojha, Animesh Kumar; Saha, Bidyut
Abstract : A low molecular weight gelator l -(+) tartaric acid- based self-healing supramolecular Cu(ii )-metallogel offers an electronic device of Schottky barrier diode at room temperature. Abstract : An ultrasonication-based copper(ii )-metallogel synthesis strategy has been developed using copper(ii )-source and l -(+)tartaric acid as a low molecular weight gelator (LMWG) in DMF medium. The rheological studies, along with the thixotropic study, established the gel material as mechanically stable and self-healable in nature. The stone-like morphological patterns of Cu(ii )metallogel were characterized through a field emission scanning electron microscopic study. The EDX elemental mapping confirms the primary chemical constituents of the metallogel. Besides, the supramolecular assembly of Cu(ii )-metallogel displays electrical conductivity on a metal–semiconductor (MS) junction electronic device. The electrical property of the metallogel was thoroughly examined. The semi-conductive characteristics like the Schottky barrier diode nature of the synthesized Cu(ii )-metallogel based device were explored.